PENGARUH PEMBELAJARAN KEWIRAUSAHAAN BERBASIS KARAKTER TERHADAP SIKAP KREATIF : Survei Pada Siswa Kelas XIIAkuntansi SMK Pasundan 1 Kota Bandung dan Siswa Kelas XII Administrasi Perkantoran SMK Negeri 1 Kota Bandung - QANITA, - (2013)
Tingkat wirausaha di Indonesia masih rendah bila dibandingkan dengan Negara berkembang lainnya. Wirausaha Indonesia kini baru mencapai sekitar 1,56 persen dari populasi penduduk, padahal dibutuhkan minimal 2 persen atau 4,8 juta wirausaha dari populasi penduduk Indonesia agar dapat berkontribusi dalam penurunan kemiskinan dan pengangguran. Tingkat pengangguran di Indonesia didominasi oleh SMK. Akibat semakin banyaknya lulusan SMK yang menganggur, semakin dirasakan pentingnya dunia wirausaha. Salah satu factor yang dapat mempengaruhi tingkat kewirausahaan di Indonesia adalah melalui dunia pendidikan yakni menerapkan pembelajaran kewirausahaan berbasis karakter. Penelitian ini bertujuan untuk 1) memperoleh temuan mengenai pelaksanaan pembelajaran kewirausahaan berbasis karakter SMK Pasundan 1 Kota Bandung dan SMK Negeri 1 Bandung. 2) memperoleh temuan mengenai sikap kreatif siswa SMK Pasundan 1 Kota Bandung dan SMK Negeri 1 Bandung, 3) memperoleh temuan mengenai pengaruh pembelajaran kewirausahaan berbasis karakter terhadap sikap kreatif siswa SMK Pasundan 1 Kota Bandung dan SMK Negeri 1 Bandung. 4) memperoleh temuan mengenai perbandingan pembelajaran kewirausahaan berbasis karakter terhadap sikap kreatif antara siswa SMK Pasundan 1 Kota Bandung dan SMK Negeri 1 Bandung. Objek yang dijadikan responden dalam penelitian ini adalah siswa kelas XII Akuntansi SMK Pasundan 1 Kota Bandung dan XII Adm. Perkantoran SMK Negeri 1 Bandung . Jenis penelitian yang digunakan adalah deskriptif dan verifikatif, metode yang digunakan adalah kuantitatif dengan metode explanatory survey dengan jumlah sampel sebanyak 77 responden. Teknik analisa data yang digunakan adalah path analysis dengan alat bantu software computer SPSS 21.0. Penelitian menunjukan bahwa hasil pengujian pembelajaran kewirausahaan berbasis karakter secara simultan memiliki pengaruh signifikan terhadap sikap kreatif. Secara parsial materi pembelajaran kewirausahaan berbasis karakter, strategi pembelajaran kewirausahaan berbasis karakter dan media pembelajaran kewirausahaan berbasis karakter memberikan pengaruh yang signifikan terhadap sikap kreatif. Sedangkan evaluasi pembelajaran kewirausahaan berbasis karakter dan guru kewirausahaan berbasis karakter secara parsial tidak memberikan pengaruh yang signifikan terhadap sikap kreatif. Dan pembelajaran kewirausahaan berbasis karakter di SMK Pasundan 1 Kota Bandung berbeda dengan SMK Negeri 1 Kota Bandung Kata Kunci : Pembelajaran Kewirausahaan Berbasis Karakter, Sikap Kreatif The level of entrepreneurship in Indonesia is low compare to other developing countries. Nowadays, Indonesia's entrepreneurs are only 1,56 per cent of population, whereas at least two per cent or 4,8 million entrepreneurs of Indonesian population are needed to contribute on decreasing poverty and unemployment. The level of unemployment in Indonesia is dominated by SMK. As an effect from unemployment of SMK graduates, the urgency of entrepreneurship is become clearer. One of the factors that can influence the level of entrepreneurship in Indonesia is through education, which is with applying entrepreneurship learning based on character. This research aims to 1) getting input about applying entrepreneurship learning based on character in SMK Pasundan 1 Bandung and SMK Negeri 1 Bandung. 2) getting input about creative attitude of students from SMK Pasundan 1 Bandung and SMK Negeri 1 Bandung, 3) getting input about the influence of entrepreneurship learning based on character towards students' creative attitude in SMK Pasundan 1 Bandung and SMK Negeri 1 Bandung. 4) getting input about the comparison between SMK Pasundan 1 Bandung and SMK Negeri 1 Bandung in case of applying entrepreneurship learning based on character. The objects of the respondents in this research are the 3rd grader of Accounting in SMK Pasundan 1 Bandung and the 3rd grader of Office Administration SMK Negeri 1 Bandung. The type of research is using descriptive and verification, while the method is using quantitative with explanatory survey method within 77 sample. In addition, path analysis is used as a form of technical data analysis using computer software SPSS 21.0. The research shows that the result of applying entrepreneurship learning based on character simultaneously give significant influence on creative attitudes. Partially, the curriculums in entrepreneurship learning based on character, the strategy within it, and media of learning, give significant influence on creative attitudes. However, the evaluation of entrepreneurship learning based on character, and the entrepreneurship teachers that teach it based on character does not give any significant impact on creative attitude. Furthermore, there are some significant differences between applying entrepreneurship learning based on character in SMK Pasundan 1 Bandung and SMK Negeri 1 Bandung. Keywords: Entrepreneurship learning based on character, creative attitude ABSTRACT Qanita ( 0900539 ), "Influence learning entrepreneurship based character with the creative ( survey on graders XII accounting SMK Pasundan 1 Bandung and graders XII Office Administration SMK 1 Bandung )." Under the guidance of Dr. H. Hari mulyadi, M.Si. Level of entrepreneurs in indonesia still low when compared with other developing countries. Entrepreneurial indonesia just now reached around 1,56 percent of population, at least 2 percent or 4.8 million entrepreneurial of indonesian population to contribute to declining poverty and unemployment. Jobless rate in indonesia is dominated by SMK. Due to many more graduates smks idle, getting perceived the importance of entrepreneurial the world. One of which could influence entrepreneurship level in indonesia is through education namely implement entrepreneurship learning based character. Research aims to 1 ) obtaining finding as to the learning entrepreneurship based character smk pasundan 1 city of bandung and public smk 1 bandung. 2 ) obtaining finding as to attitude creative smk student pasundan 1 city of bandung and public smk 1 bandung, 3 ) obtaining finding as to influence learning entrepreneurship based character with the creative smk student Pasundan 1 city of Bandung and public SMK 1 Bandung. object used as respondents in this research is on graders XII accounting SMK Pasundan 1 Bandung and graders XII Office Administration SMK 1 Bandung. The kind of research used is descriptive and verifikatif, methods used is quantitative by method explanatory survey by the number of samples about 77 respondents. Technical data analysis used is the path analysis test comparison 2 variable free ( test t ) with aids computer software spss 21.0. Research showed that the testing learning entrepreneurship based character simultaneously have influence significantly to attitude creative. In partial matter learning entrepreneurship based character, entrepreneurship learning strategy based character and media learning entrepreneurship based character exert significant with the creative. While entrepreneurship learning evaluation based character and teacher entrepreneurship based character in partial not exerting influence significant with the creative. Password: Learning Entrepreneurship Based Character, Attitude Creative